Fingerprinting the Lamb Wave Signals by Using S-Transformation - (:unkn) unknown (SPIE-INT SOC OPTICAL ENGINEERING, 2012)
Lamb wave method detects the defects from the propagation characteristics of the created brief harmonic signals. Generally, the defects are detected by analyzing the delays and amplitudes of the received waves. The envelopes of the sensory signals may be used to calculate the delays and amplitudes of the received signals. Sometimes, similar envelopes could be observed at different test conditions. Use of the time-frequency spectra of the s-transformation is proposed for distinction of the problems when the envelopes of the monitored signals are very similar. In the study, a beam was compressed from different points with a hydraulic crimping tool. In separate tests, the cross sectional area at the middle of the beam was reduced by opening slots. The envelopes and time-frequency spectra of the sensory signals were calculated by using the s-transformation. The difference of the time-frequency spectra successfully distinguished the test condition when the envelopes were very similar.
Keywords: SHM; damage detection; Lamb wave SHM; s-transformation; DAMAGE; LOCALIZATION